2015
DOI: 10.1038/ajg.2014.417
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Lynch Syndrome Screening by Microsatellite Instability in Patients ≤50: Prevalence, Testing Determinants, and Result Availability Prior to Colon Surgery

Abstract: Despite frequently abnormal MSI/IHC results, LS screening in young, high-risk patients is low. Provider education and disparities in access to specialized services, particularly in underserved populations, are possible contributors. MSI/IHC results are infrequently available preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
2
31
2
Order By: Relevance
“…The prevalence of LS in our diverse patient population was 1.9 %, which is similar to the prevalence in the largest pooled screening study (Pinol et al 2005), though because less than 40 % of patients met LS screening criteria in our study this likely leads to a low estimate of the true prevalence. Furthermore, given the results of a recent state-level database study from Louisiana (Karlitz et al 2015) showing public hospitals were the least likely to test for MSI in young CRC patients, the favorable outcomes we demonstrate provide a framework for LS screening implementation that may be applicable to other safety net hospitals.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The prevalence of LS in our diverse patient population was 1.9 %, which is similar to the prevalence in the largest pooled screening study (Pinol et al 2005), though because less than 40 % of patients met LS screening criteria in our study this likely leads to a low estimate of the true prevalence. Furthermore, given the results of a recent state-level database study from Louisiana (Karlitz et al 2015) showing public hospitals were the least likely to test for MSI in young CRC patients, the favorable outcomes we demonstrate provide a framework for LS screening implementation that may be applicable to other safety net hospitals.…”
Section: Discussionmentioning
confidence: 80%
“…However, implementation requires a multidisciplinary approach with close integration of clinical services and genetic testing is a complex and delicate matter (Ladabaum 2014). Furthermore, in resource-limited settings, screening only higher risk patients may be practical and there is considerable variation in the implementation of genetic screening in community hospitals (Cohen 2014;Karlitz et al 2015). With the passage of the Affordable Care Act and the expansion of health insurance coverage, an increasing number of previously underserved patients seek medical care at safety net hospitals and further understanding of LS in this patient population is critical.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned study examined several testing factors associated with an increased likelihood of undergoing LS screening including family history of CRC, residence in an urban setting and receiving care at a comprehensive cancer center [8]. The positive effect of family history may be obvious, but what can be made of urban location and treatment center influence?…”
mentioning
confidence: 99%
“…Studies have demonstrated the rate of metachronous lesions to drop significantly (postoperative risk is 0-3.4 %) when the recommended surgical intervention was performed [6,7]. Given this expanding appreciation for the role that genetic analysis may play in CRC surgical and medical management, the expectations would be for a rise in genetic evaluation, unfortunately the reality seems far from it.A recent study utilizing CDC comparative effectiveness research data conducted by our group evaluated the frequency of MSI and IHC testing in early-onset CRC patients and availability of testing results preoperatively [8]. The study, which was the first population-based study in the USA to evaluate LS screening practices, took place in Louisiana, which was recently demonstrated to have one of the highest incidence rates of CRC in the USA and very high rates of early-onset CRC, particularly in certain regions [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation